A Sociocultural Perspective of Adult Literacy: Ethnographic Analysis of the Instructional Practices of Two Adult Education Tutors in Indonesia - Irmawita Irmawita; Vevi Sunarti; Ciptro Handrianto; Shahid Rasool; Sabbir Ahmed Chowdhury (JETL (Journal of Education, Teaching and Learning), 2025)
This study focuses on the topic of emerging adult literacy in Indonesia by investigating the sociocultural perspective of tutors who involved in the program. This study adopts a sociocultural perspective and presents an ethnographic investigation that examines the instructional practices of two adult education tutors. In-depth and repeated interviews were conducted with the two subjects to learn about their socioeconomic situation, teaching and training history, personal motivation, literacy beliefs, and pedagogical philosophy. The results of this study, which looked at two tutors' literacy instruction in terms of their characteristics and attitudes as well as their working environments, have shown the benefits of adopting a social perspective on teaching. The findings show that these two tutors are highly motivated and committed to helping their students learn to read and write despite the challenges they face as tutors, including a lack of thorough pre-service, limited in-service training, and minimal ongoing financial and pedagogical support. The results of this research could potentially have significant consequences for developing more efficient adult literacy initiatives in Indonesia and similar culturally heterogeneous environments.